The SCO4117 ECF Sigma Factor Pleiotropically Controls Secondary Metabolism and Morphogenesis in Streptomyces coelicolor - López-García, María T.; Yagüe, Paula; González-Quiñónez, Nathaly; Rioseras, Beatriz; Manteca, Angel (Frontiers in Microbiology, 2018)
Extracytoplasmic function (ECF) sigma factors are a major type of bacterial signal-transducers whose biological functions remain poorly characterised in streptomycetes. In this work we studied SCO4117, a conserved ECF sigma factor from the ECF52 family overexpressed during substrate and aerial mycelium stages. The ECF52 sigma factors harbour, in addition to the ECF sigma factor domain, a zinc finger domain, a transmembrane region, a proline-rich C-terminal extension and a carbohydrate-binding domain. This class of ECF sigma factors is exclusive to Actinobacteria. We demonstrate that SCO4117 is an activator of secondary metabolism, aerial mycelium differentiation and sporulation, in all the culture media (sucrose-free R5A, GYM, MM and SFM) analysed. Aerial mycelium formation and sporulation are delayed in a SCO4117 knockout strain. Actinorhodin production is delayed and calcium-dependent antibiotic production is diminished, in the ΔSCO4117 mutant. By contast, undecylprodigiosin production do not show significant variations. The expression of genes encoding secondary metabolism pathways (deoxysugar synthases, actinorhodin biosynthetic genes) and genes involved in differentiation (rdl, chp, nepA, ssgB) was dramatically reduced (up to 300-fold) in the SCO4117 knockout. A putative motif bound, with the consensus “CSGYN-17bps-SRHA” sequence, was identified in the promoter region of 29 genes showing affected transcription in the SCO4117 mutant, including one of the SCO4117 promoters. SCO4117 is a conserved gene with complex regulation at the transcriptional and post-translational levels and the first member of the ECF52 family characterised.